Education Management Study on the Institutionalization of Islamic Education - Totok Fuby Purwanto; Yayat Suharyat (International Journal of Global Sustainable Research, 2023)
The school implements teaching administration for its students and is an official educational institution. Apart from formal education, there is also non-formal education, such as Islamic education, which uses modern educational administration to try to direct education in the right direction. The ideals and character of Islamic society are largely shaped by Islamic education. One important component in producing high quality and long-lasting Islamic education is educational administration. This paper uses a qualitative library research methodology. Collecting journals regarding this matter with the aim of collecting data and knowledge about educational management is known as library research. The function of educational management in the process of institutionalizing Islamic education is examined in this essay. This includes planning, organizing, curriculum development, resource management, and assessment of Islamic educational institutions. The findings of this research provide an explanation of how educational administration can influence how well Islamic teaching is institutionalized.